Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L.; Cotti, C.; Cristofolini, G. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were employed to examine samples from Quercus cerris, Q. suber and Q. crenata in order to test the hypothesis of the hybrid origin of Q. crenata from Q. cerris and Q. suber in a part of its distribution area where the two putative parents do not overlap at present. Leaves from 21 Q. crenata and 37 Q. cerris individual trees were collected at natural sites in northern Italy, where Q. suber is currently lacking; 21 Q. suber and six Q. crenata plants from central Italy were also analysed. Results from Unweighted Pair Group Method with Arithmetic mean (UPGMA) analysis and principal component analysis (PCA) implied that exchange of neutral markers has been considerable between the three species, while differences in morphological characters have remained comparatively stable. The Mantel test indicated low correlation between RAPD- and ISSR-based similarity matrices, showing that the two screening techniques reveal unrelated estimates of genetic relationships. Hybrid indices computed for both markers displayed an intermediate position of Q. crenata individuals between the two putative parents shifted toward Q. cerris. Results from the present study corroborate the hypothesis of a hybrid origin for Q. crenata occurring in northern Italy, and suggest asymmetrical backcrossing with Q. cerris acting as the recurrent parent.
From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: DNA markers; Hybridization; introgression; ISSR; RAPD

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were employed to examine samples from Quercus cerris, Q. suber and Q. crenata in order to test the hypothesis of the hybrid origin of Q. crenata from Q. cerris and Q. suber in a part of its distribution area where the two putative parents do not overlap at present. Leaves from 21 Q. crenata and 37 Q. cerris individual trees were collected at natural sites in northern Italy, where Q. suber is currently lacking; 21 Q. suber and six Q. crenata plants from central Italy were also analysed. Results from Unweighted Pair Group Method with Arithmetic mean (UPGMA) analysis and principal component analysis (PCA) implied that exchange of neutral markers has been considerable between the three species, while differences in morphological characters have remained comparatively stable. The Mantel test indicated low correlation between RAPD- and ISSR-based similarity matrices, showing that the two screening techniques reveal unrelated estimates of genetic relationships. Hybrid indices computed for both markers displayed an intermediate position of Q. crenata individuals between the two putative parents shifted toward Q. cerris. Results from the present study corroborate the hypothesis of a hybrid origin for Q. crenata occurring in northern Italy, and suggest asymmetrical backcrossing with Q. cerris acting as the recurrent parent.
From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)